2022
DOI: 10.1136/bmjopen-2021-051568
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of ultrasound, CT and their combination in detecting cervical lymph node metastasis in patients with papillary thyroid cancer: a systematic review and meta-analysis

Abstract: ObjectivesTo determine the diagnostic accuracy of ultrasound (US), CT and their combination in detecting cervical lymph node metastasis (CLNM) in patients with papillary thyroid cancer (PTC).MethodsMedline (via PubMed), Web of Science, Embase were searched to identify studies published till 5 December 2021 that used US and CT to detect CLNM in patients with PTC. The primary outcomes were sensitivity, specificity and diagnostic ORs in neck-level-based (lymph nodes are analysed by neck level) or patient-based (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…According to the latest ATA guidelines from 2015 ( 9 ), prophylactic lateral lymph node resection is not recommended for patients with PTC without evidence of LLNM on clinical examination or imaging. Tragically, ultrasound/computed tomography is highly specific but of low sensitivity in identifying LLNM ( 7 , 21 ), and a 30% false-negative-rate for benign fine-needle-aspiration-biopsy results has been reported ( 22 ). Moreover, occult LLNM may occur and not be detected by preoperative regular examination ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the latest ATA guidelines from 2015 ( 9 ), prophylactic lateral lymph node resection is not recommended for patients with PTC without evidence of LLNM on clinical examination or imaging. Tragically, ultrasound/computed tomography is highly specific but of low sensitivity in identifying LLNM ( 7 , 21 ), and a 30% false-negative-rate for benign fine-needle-aspiration-biopsy results has been reported ( 22 ). Moreover, occult LLNM may occur and not be detected by preoperative regular examination ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, preoperative ultrasonography and computed tomography for screening suspected cervical LLNM are highly specific but of low sensitivity, particularly in the evaluation of occult LLNM, which are of limited value ( 7 ). Lateral lymph node dissection is not recommended unless suspicious LLNM is confirmed by preoperative imaging and fine needle aspiration biopsy (FNAB).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies demonstrate that experience greater than seven years increases the positive predictive value and confidence of LNM detection [ 58 ]. While other meta-analyses have shown differences in diagnostic testing accuracy of US versus CT staging, our study is the first to search and analyze the literature for differences in US staging performed by radiologists compared to non-radiologists [ 45 , 59 ]. Our work found that US performed by radiologists were of similar diagnostic accuracy ( p = 0.517) as those performed by non-radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) is a rst-line noninvasive imaging method for preoperative evaluation of cervical lymph node status. The current research says that the diagnostic ability of ultrasound in lateral cervical lymph nodes is higher than that of computed tomography (CT) or its combination [7]. However, due to the interference of bone and gas or the in uence of operator's level, the sensitivity of ultrasound to lymph node metastasis in lateral neck region is different [8].…”
Section: Introductionmentioning
confidence: 99%